Addressing Disparities in Low Back Pain Care by Developing Culturally Appropriate Information for Aboriginal Australians: "My Back on Track, My Future". Issue 11 (13th January 2017) - Lin, Ivan B.; Ryder, Kim; Coffin, Juli; Green, Charmaine; Dalgety, Eric; Scott, Brian; Straker, Leon M.; Smith, Anne J.; O'Sullivan, Peter B.
Abstract: Objectives: Addressing disparities in low back pain care (LBP) is an important yet largely unaddressed issue. One avenue to addressing disparities, recommended by clinical guidelines, is to ensure that LBP information is culturally appropriate. Our objectives were, first, to develop LBP information that was culturally appropriate for Aboriginal Australians living in a rural area and, second, to compare this to traditional information. Methods: The overall information development process was guided by a "cultural security" framework and included partnerships between Aboriginal/non-Aboriginal investigators, a synthesis of research evidence, and participation of a project steering group consisting of local Aboriginal people. LBP information (entitled My Back on Track, My Future [MBOT]) was developed as five short audio-visual scenarios, filmed using Aboriginal community actors. A qualitative randomized crossover design compared MBOT with an evidence-based standard (the Back Book [BB]). Twenty Aboriginal adults participated. Qualitatively we ascertained which information participants' preferred and why, perceptions about each resource, and LBP management. Results: Thirteen participants preferred MBOT, four the BB, two both, and one neither. Participants valued seeing "Aboriginal faces, " language that was understandable, the visual format, and seeing Aboriginal people undertaking positive changes in MBOT. In contrast, many participants found the language and format of the BB a barrier. Participants who preferred the BB were more comfortable with written information and appreciated the detailed content. Conclusions: The MBOT information was more preferred and addressed important barriers to care, providing support for use in practice. Similar processes are needed to develop pain information for other cultural groups, particularly those underserved by existing approaches to care.